The Application of Brain Organoids in Assessing Neural Toxicity - Fan, Pan; Wang, YuanHao; Xu, Min; Han, Xiao; Liu, Yan (Frontiers in Molecular Neuroscience, 2022)
Human brain is a complicated and precise organized organ. Exogenous chemicals, such as pollutants, drug and industrial chemicals may affect the biological progress of brain or its function and eventually lead to neurological diseases. Animal model may not fully recapitulate human brain to testing neural toxicity. Brain organoids with self-assembled three-dimensional(3D) structure, provide opportunities to generate relevant to test or prediction human neurotoxicity. Here we reviewed recent advances in brain organoid techniques and its application in accessing neural toxicants. We hope this review could provide new insights for further progress of brain organoid application in neural toxicant screen studies.